Association of COMT Val158Met polymorphism and breast cancer risk: an updated meta-analysis - Qin Xue; Peng Qiliu; Qin Aiping; Chen Zhiping; Lin Liwen; Deng Yan; Xie Li; Xu Juanjuan; Li Haiwei; Li Taijie; Li Shan; Zhao Jinmin (Diagnostic Pathology, 2012)
Abstract Background Catechol-O-methyltransferase (COMT) is one of the most important enzymes involved in estrogen metabolism and its functional genetic polymorphisms may be associated with breast cancer (BC) risk. Many epidemiological studies have been conducted to explore the association between the COMT Val158Met polymorphism and breast cancer risk. However, the results remain inconclusive. In order to derive a more precise estimation of this relationship, a large meta-analysis was performed in this study. Methods Systematic searches of the PubMed, Embase and Cochrane Library were performed. Crude odds ratios (ORs) with 95% confidence intervals (CIs) were calculated to estimate the strength of the association. Results A total of 56 studies including 34,358 breast cancer cases and 45,429 controls were included. Overall, no significant associations between the COMT Val158Met polymorphism and breast cancer risk were found for LL versus HH, HL versus HH, LL versus HL, recessive model LL versus HL+HH, and dominant model LL+HL versus HH. In subgroup analysis by ethnicity, source of controls, and menopausal status, there was still no significant association detected in any of the genetic models. Conclusion Our meta-analysis results suggest that the COMT Val158Met polymorphism may not contribute to breast cancer susceptibility. Virtual slides The virtual slides(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs4806123577708417